King's eaudiobook - Pamfiloff, Mimi Jean (King Trilogy, 2015)
When Mia Turner's brother goes missing in Mexico, while on an archaeological dig, she believes that life couldn't get much worse. But when she's blocked at every turn from finding answers, by both local and U.S. authorities, she must turn to a man she swears is the devil. Others might be fooled by his private jet, fine tailored suits, and disarming smile, but Mia knows something dark, sinister, and unnatural lurks behind those penetrating, pale-gray eyes. And the more she learns, the more she realizes she may never be free again. Contains mature themes.